Bioavailability of iron and zinc in green leafy vegetables growing in river side and local areas of Allahabad district - Srivastava, Bhawna; Verma, Anisha; ., Neerubala (Indian Journal of Community Health, 2015)
Introduction: Green Leafy Vegetables (GLVs) are the treasure trove of many micronutrients. Objective: The aim of the study is to find out the commonly growing vegetables in river side and local areas of Allahabad district and to access the bioavailability of iron and zinc in selected green leafy vegetables of river side and local areas of Allahabad district. Methods: Five to four commonly grown green leafy vegetables were selected from the Arailghat, Baluaghat, Gaughat, Mahewa, Muirabad, Rajapur, Rasullabad for the study. Total iron and zinc in sample were estimated by AOAC (2005) and bioavailability of zinc and iron from various food samples was determined in vitro method described by Luten (1996). Appropriate statistical technique was adopted for analysis of study. Result: Soya leaves, Radish leaves, Amaranth, Spinach were grown in both the areas except Kulpha and Karamwa, which are commonly grown in river side area. There was a significant difference between the bioavailability of iron and zinc in GLV grown in local and river side area. Conclusion: Hence it can be concluded that there is a contamination of heavy metals which binds with the iron and zinc and make them less bioavailable in the selected GLV.